Potential role of tocotrienols in the treatment and prevention of breast cancer. (27th June 2013) - Sylvester, Paul W.; Akl, Mohamed R.; Malaviya, Abhita; Parajuli, Parash; Ananthula, Suryatheja; Tiwari, Roshan V.; Ayoub, Nehad M.
Abstract Vitamin E is a generic term that refers to a family of compounds that is further divided into two subgroups called tocopherols and tocotrienols. Although all natural forms of vitamin E display potent antioxidant activity, tocotrienols are significantly more potent than tocopherols in inhibiting tumor cell growth and viability, and anticancer activity of tocotrienols is mediated independently of their antioxidant activity. In addition, the anticancer effects of tocotrienols are observed using treatment doses that have little or no effect on normal cell function or viability. This review will summarize experimental studies that have identified the intracellular mechanism mediating the anticancer effects of tocotrienols. Evidence is also provided showing that combined treatment of tocotrienol with other cancer chemotherapies can result in a synergistic inhibition in cancer cell growth and viability. Taken together, these findings strongly indicate that tocotrienols may provide significant health benefits in the prevention and/or treatment of cancer when used either alone as monotherapy or in combination with other anticancer agents. © 2013 BioFactors, 40(1):49–58, 2014